Asteroseismic inferences on GW Virginis variable stars in the frame of new PG 1159 evolutionary models - Córsico, Alejandro Hugo (2006)
An adiabatic, nonradial pulsation study of GW Vir stars is presented. The pulsation calculations were based on PG 1159 evolutionary sequences with different stellar masses artificially derived from a full evolutionary sequence of 0.5895 M⊙ that has been computed by taking the evolutionary history of the progenitor star into account. The artificial sequences were constructed by appropriately scaling the stellar mass of the 0.5895-M ⊙ sequence well before the models reached the low-luminosity, high-gravity stage of the GW Vir domain. We computed g-mode pulsation periods appropriate to GW Vir variable stars. The implications for the mode-trapping properties of our PG 1159 models are discussed at length. We found that the mode-trapping features characterizing our PG 1159 models are mostly fixed by the stepped shape of the core chemical profile left by prior convective overshooting. This is particularly true at least for the range of periods observed in GW Vir stars. In addition, we make asteroseismic inferences about the internal structure of the GW Vir stars PG 1159-035, PG 2131+066, PG 1707+427, and PG 0122+200.